1997
DOI: 10.1128/jb.179.4.1329-1336.1997
|View full text |Cite
|
Sign up to set email alerts
|

Expression, inducer spectrum, domain structure, and function of MopR, the regulator of phenol degradation in Acinetobacter calcoaceticus NCIB8250

Abstract: Degradation of phenol by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
109
0
5

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(118 citation statements)
references
References 45 publications
4
109
0
5
Order By: Relevance
“…3). In agreement with these data, in vivo inhibition of derivatives of the cognate regulator by overexpression of the A-domains of XylR (Perez-Martin and de Lorenzo, 1995a) and MopR (Schirmer et al, 1997) in trans have recently been shown to be unaffected by the addition of effectors. Hence, for DmpR and, in all probability, for XylR and MopR, effector nonresponsiveness of the physically uncoupled A-domain is an intrinsic property.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…3). In agreement with these data, in vivo inhibition of derivatives of the cognate regulator by overexpression of the A-domains of XylR (Perez-Martin and de Lorenzo, 1995a) and MopR (Schirmer et al, 1997) in trans have recently been shown to be unaffected by the addition of effectors. Hence, for DmpR and, in all probability, for XylR and MopR, effector nonresponsiveness of the physically uncoupled A-domain is an intrinsic property.…”
Section: Discussionsupporting
confidence: 65%
“…Similarly, the DNA binding properties of 70 and related sigma factors are also under repression control (Dombroski et al, 1993). DmpR (Shingler and Pavel, 1995) belongs to a mechanistic subgroup of 54 -dependent regulators, which includes XylR (Delgado et al, 1995;Ferná ndez et al, 1995), MopR (Schirmer et al, 1997), DctD (Gu et al, 1994), FhlA (Korsa and Bö ck, 1997) and RocR (Gardan et al, 1997), in which deletion and/or mutation analysis has implicated intramolecular repression as a common control mechanism (for review, see Shingler, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primers used for amplification of the ptsH gene were KS 34 (5h-AAAGTCGACATGAAGAAGATTCAA GTAGTCGTTAAAGAC-3h) and KS 35 (5h-AAAAAGCTTT TAAATAACTTGGTGTTTTTCTAAAACTGC-3h). The PCR products were digested with SalI and HindIII, and the resulting fragments were cloned into the expression vector pWH844 (Schirmer et al, 1997) cut with the same enzymes. The resulting plasmids were pGP204 (for hprK) and pGP217 (for ptsH).…”
Section: Methodsmentioning
confidence: 99%
“…Plasmid pHisG4032 was constructed by insertion of a 573 bp BamHI-HindIII fragment carrying expG of S. meliloti 2011 (Casse et al, 1979) into vector pWH844 (Schirmer et al, 1997). This Fragment was amplified by PCR with primer HisG5 (5 0 -AAAAGGATCCAT GAACCACAGGATACTCTATCCGT, BamHI restriction site is underlined) and HisG3 (5 0 -AAAA AAGCTTCATGTTACCGCCCTTGCTCG, HindIII restriction site is underlined) from pARIIa .…”
Section: Bacterial Strains Plasmids and Growth Conditionsmentioning
confidence: 99%